1984
DOI: 10.1093/ajcn/40.4.808
|View full text |Cite
|
Sign up to set email alerts
|

New standards of weight and body composition by frame size and height for assessment of nutritional status of adults and the elderly

Abstract: The study includes measurements of height, weight, triceps skinfold, subscapular skinfold, upper arm circumference, and elbow breadth of a cross-sectional multiracial sample of 21,752 subjects aged 25 to 74 yr derived from the data sets of the first and second National Health and Nutrition Examination Surveys (NHANES I and NHANES II). Based on these data, percentiles of weight, skinfolds, and bone-free upper arm muscle area by height, sex, and frame size were established for all races combined in two groups: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
243
1
39

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(288 citation statements)
references
References 12 publications
5
243
1
39
Order By: Relevance
“…They would seem the ideal tool for assessing nutrition in elderly people in the community. In younger groups the usefulness of anthropometric data depends on sex-related reference standards being available for comparison but local databases are necessary because genetic and environmental factors in¯uence indices (Frisancho, 1984). However knowledge of the use of anthropometric data or its application in very old age is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They would seem the ideal tool for assessing nutrition in elderly people in the community. In younger groups the usefulness of anthropometric data depends on sex-related reference standards being available for comparison but local databases are necessary because genetic and environmental factors in¯uence indices (Frisancho, 1984). However knowledge of the use of anthropometric data or its application in very old age is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, these dif®culties were minimised by attention to measurement techniques and subject recruitment. Percentiles for triceps skin fold have been developed for ages 55±74 y in America (Frisancho, 1984), in Canada (Nutrition, Canada, 1980, in Britain to age 85 y (Burr and Phillips, 1984) but not the b 90 y group. The SENECA study demonstrated the wide range of sex-related TSF values possible within genetically and economically diverse 75 y old European groups.…”
Section: Discussionmentioning
confidence: 99%
“…Skinfold thicknesses (biceps, triceps, suprailiac, subscapular) were measured twice using a Harpenden skinfold caliper at 5 min intervals at each site following a standardized technique. 46 Sagittal abdominal diameter was measured at the L 4-5 level in the supine position and waist girth was also measured. Anthropometric variables were measured by a single investigator.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Since that time, Roberto's influential publications have helped to make the use of anthropometric norms commonplace in the fields of nutritional science and public health. Indeed, Roberto's three most widely cited refereed publications (each cited more than 200 times) are papers on anthropometric standards that were published in the American Journal of Clinical Nutrition (Frisancho, 1974(Frisancho, , 1981b(Frisancho, , 1984. These norms have been widely reprinted in introductory and advanced texts in human nutrition (e.g., Duggan, 2008;Edelstein, 2007;Gibson, 2005;Samour, 2005), and his own books-Anthropometric Standards for the Assessment of Growth and Nutritional Status (Frisancho, 1990), and the recently published Anthropometric Standards: An Interactive Nutritional Reference of Body Size and Body Composition for Children and Adults (Frisancho, 2008) are standard reference texts in both human biology and human nutritional science.…”
Section: ''The Growth Of Growth'': Anthropmetric Standards and Nutritmentioning
confidence: 99%